Pengaruh Pemberian Leaflet Terhadap Tingkat Kepatuhan Minum Obat pada Pasien Diabetes Melitus Tipe-2 di Puskesmas Guntung Manggis - Siti Khadijah; Helmina Wati; Aristha Novyra Putri (BORNEO JOURNAL OF PHARMASCIENTECH, 2023)
Type 2 diabetes mellitus is a metabolic disorder characterized by increased blood glucose levels (hyperglycemia) due to decreased insulin secretion by pancreatic beta cells or impaired insulin function. Compliance with taking medication is very important to achieve therapeutic success and prevent complications by providing education using leaflets so as to increase understanding of treatment instructions. The purpose of this study was to determine the effect of giving leaflets on the level of medication adherence and blood glucose levels during (BGLD) in patients with type-2 diabetes mellitus at the Guntung Manggis Health Center. This study used a quasi-experimental design method with a pretest-posttest duo grub approach using the MMAS-8 questionnaire. Sampling was taken prospectively with a total of 88 patients divided into 2 intervention and control groups. There were differences in the level of adherence to taking medication before being given the leaflet as many as 26 respondents were in the adherent category and increased to 43 respondents after being given the leaflet. The results of the study obtained an average value of BGLD before being given a leaflet of 281 mg/dL and after being given a leaflet of 262 mg/dL. The statistical test results showed that there was an effect of giving leaflets on adherence to taking medication in patients with type-2 DM at the Guntung Manggis Health Center with a p-value of 0.001 <0.05 and a BLD value of 0.000 <0.05